PRODUCTION OF PARTICLEBOARD PANELS FROM WOOD OF Ochroma pyramidale - Stange, Rafaela; Vieira, Helena Cristina; Mattos, Maísa Beatriz Koch; Muzeka, Luran Monteiro; Monteiro, Thiago Campos; Rios, Polliana D'Angelo (Floresta, 2024)
The objective of this work was to evaluate the use of the species O. pyramidale for the production of particleboards. The trees, aged 6 years, came from the Municipality of Mira Estrela/SP state. The logs were peeled and processed in an industrial chopper to obtain particles. Eight treatments were carried out, varying the levels of paraffin emulsion (0, 1, 1.5 and 2%), and the levels of urea formaldehyde adhesives (10 and 12%). The particles went through a drying process until they reached 4% moisture. For pressing the panels, the parameters temperature of 160°C, specific pressure of 30 kgf/cm² and time of 10 minutes were used. The panels were tested by physical tests and mechanical tests, all following the procedures of the following standards: D-1037 (ASTM, 2006) for density, water determination and thickness increase and internal connection; DIN 52362 (1982) for parallel static bending. As a result, it was concluded that the increased addition of paraffin to the panels resulted in an improvement in their dimensional stability. The treatment that added 12% urea formaldehyde adhesive and 1.5% paraffin achieved superior results in mechanical properties, equivalent to 10390.91kgf cm-2 for the separation modulus, 101.46kgf cm-2 for the rupture modulus. The O. pyramidale particleboards reached the minimum values of 1.4 kgf/cm² for internal bonding and 56 kgf/cm² for the modulus of rupture required by CS 235-66 (1968), thus becoming a potential species for the production of particleboard panels.